2015
DOI: 10.1016/j.colsurfa.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation study of sodium dodecyl sulfate micelle: Water penetration and sodium dodecyl sulfate dissociation

Abstract: h i g h l i g h t s• SDS micelle was simulated for 20 ns using all-atom MD simulation.• SDS conformations are mostly bent in micelle.• Free volume in SDS micelle is ∼0.35% of the micelle volume.• Free energy change for water penetration through SDS micelle is ∼10 kcal/mol.• Dissociation of a single SDS molecule from the micelle requires ∼13 kcal/mol. g r a p h i c a l a b s t r a c t a b s t r a c tWe investigate a micelle consisting of 60 sodium dodecyl sulfate (SDS) molecules in water phase using molecular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 78 publications
9
41
0
Order By: Relevance
“…In contrast, in the slightly smaller DTAC micelle, even though a similar bent conformation is observed, the tails tend to remain directed towards the micelle centre. The SDS micelle was found to be stable over the entire MD trajectory at three selected temperatures, in agreement with the previous MD study by Jang and co‐workers which reported that external energy of ≈13 kcal mol −1 was required for the dissociation of the SDS molecules . Conversely, our results show that in the DTAC micelle individual molecules temporarily dissociate spontaneously, albeit infrequently.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, in the slightly smaller DTAC micelle, even though a similar bent conformation is observed, the tails tend to remain directed towards the micelle centre. The SDS micelle was found to be stable over the entire MD trajectory at three selected temperatures, in agreement with the previous MD study by Jang and co‐workers which reported that external energy of ≈13 kcal mol −1 was required for the dissociation of the SDS molecules . Conversely, our results show that in the DTAC micelle individual molecules temporarily dissociate spontaneously, albeit infrequently.…”
Section: Resultssupporting
confidence: 92%
“…An eccentricity of 0 indicates a perfect sphere. The averaged over time eccentricity of the SDS micelle was 0.118±0.035, which falls within the range of previously reported values obtained from MD simulations (0.057–0.154). Experimentally, the shape of the SDS micelle is still a topic of debate, with scattering data consistent with both slightly prolate and oblate spheroids .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Most of the commonly used surfactants form micelles with radii of curvature close to the length of their hydrocarbon chains [10]. The structure, thermodynamics, and dynamic properties of aggregates or films of amphiphilic molecules are of prime importance in a great variety of systems [11–16]. …”
Section: Introductionmentioning
confidence: 99%
“…Even though the micelles from SLS tend to expose the hydrocarbon chains (hydrophobic) on its external surface, due to the lower amount of the sulfate radical, it has been shown that they allow the entrance of water into its interior [Chun et al, 2015].…”
Section: Influence Of Surfactants On Dental Erosionmentioning
confidence: 99%